Hijrah in the Sufisme Perspective: Study of Religious Phenomenology on the Role and Activities of Da'wah of Youth Hijrah in Cirebon - Atamimi, Abdul Basit; Muaz, Abdul; Handayani, Afni (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This article aims to describe and analyze Islamic thinking about the phenomenon of Youth Hijrah in society. The term is used as an expression of the phenomenon of people who are new to or pay attention to Islam after paying little attention to it before. This research is aimed at answering how Islamic thoughts and views regarding Youth Hijrah, historical roots, the role, and da'wah activities of the Youth Hijrah are associated with the diversity of society in Cirebon. This research was conducted to find out, and analyze about; 1) Islamic thoughts and views on Youth Hijrah, 2) the Historical roots, role, and da'wah activities of Youth Hijrah in Cirebon, 3) The concept of religious phenomenology towards Youth Hijrah in Cirebon. The research approach used is qualitative. The method used is analytical descriptive. The results of this study are: First, Hijrah means